Growth and β-galactosidase activity in cultures of Kluyveromyces marxianus under increased air pressure - Pinheiro, Rita (2003)
Aims: To investigate the effect of total air pressure raise on cell growth and intracellular β-galactosidase activity in batch cultures of Kluyveromyces marxianus CBS 7894. Methods and Results: A pressurized bioreactor was used for K. marxianus batch cultivation under increased air pressure from 1.2 to 6 bar. Under these conditions no inhibition of cell growth was observed. Moreover, the improvement of the oxygen transfer rate (OTR) from the gas to the culture medium by pressurization led to an enhancement of the cell growth rate obtained at atmospheric pressure without aeration. The specific β-galactosidase productivity increased from 5.8 to 17.0 U gCDˉ¹ hˉ¹ using a 6-bar air pressure instead of air at atmospheric pressure. The antioxidant enzyme superoxide dismutase (SOD) was slightly induced by the air pressure raise, which indicates that the defensive mechanisms of the cells can cope with an air pressure up to 6 bar. Conclusions: These experiments showed that the increase of air pressure up to 6 bar is an alternative to other methods of preventing the oxygen limitation and can be applied in the β-galactosidase production by K. marxianus. Significance and Impact of the Study: The results here reported proved that, in what biological aspects are concerned, it is possible to use the air pressure increase as an optimization parameter of β-galactosidase production in high-density cell cultures of K. marxianus strains.